An investigation into the crashworthiness criteria of a top-hat structure with a dent-type crush initiator through numerical analysis - Purnama, Harry (Jurnal Polimesin, 2023)
Ensuring the safety of passengers and the battery compartment in electric vehicles during frontal collisions is of utmost importance. This research aims to enhance the design of the top-hat structure used in car front rails by incorporating a crush initiator as the weakest section. The addition of a crush initiator optimizes the crashworthiness criteria by reducing peak force and increasing energy absorption. Numerical simulations were conducted using ABAQUS to validate the findings and compared against experimental results from references. The results demonstrate that the development of a top-hat structure with a dent-type crush initiator led to 27.5% decrease in peak force and 18.75% increase in energy absorption. The improvements in peak force and energy absorption could reduce the impact force and allow the crumple zone to completely absorb the kinetic energy during a collision, positively affecting the safety of passengers and battery compartments in electric vehicles